Вместо звездочки вставьте нужный множитель,чтобы получилось верное равенство: 1)9х²+3*=3х(3х+1); 2)2*б -- *б²=аб(2-б) 3)4*у -х*=ху(4х³--у) 4)**- 3у^5=у^5(х²-3) 5)3б^2a^3-ab^3=ab^2(*a^2-*) 6) 28a^3B-4A^2B^3=**(7A-B*)
Вместо звездочки вставьте нужный множитель,чтобы получилось верное равенство:
1)9х²+3*=3х(3х+1);
2)2*б -- *б²=аб(2-б)
3)4*у -х*=ху(4х³--у)
4)**- 3у^5=у^5(х²-3)
5)3б^2a^3-ab^3=ab^2(*a^2-*)
6) 28a^3B-4A^2B^3=**(7A-B*)
Ответ(ы) на вопрос:
Гость
[latex]9x^2+3*=3x(3x+1)\\ 3x^2+3x=9x^2+3x\\\\ 2*b-*b^2=ab(2-b)\\ 2ab-2b^2=2ab-2b^2\\\\ 4*y-x*=xy(4x^3-y)\\ 4x^4y-xy^2=4x^4y-xy^2\\\\ **-3y^5=y^5(x^2-3)\\ x^2y^5-3y^5=x^2y^5-3y^5\\\\ 3b^2a-ab^3=ab^2(*a^2-*)\\ ab^2(3a^2-b)=ab^2(3a^2-b)\\\\ 28a^3b-4a^2b^3=**(7a-b^{*})\\\\ 4a^2b(7a-b^2)=4a^2b(7a-b^2)[/latex]
Не нашли ответ?
Похожие вопросы